2020
DOI: 10.1111/1755-0998.13211
|View full text |Cite
|
Sign up to set email alerts
|

A demonstration of conservation genomics for threatened species management

Abstract: As species extinction rates increase, genomics provides a powerful tool to support intensive management of threatened species. We use the Tasmanian devil (Sarcophilus harrisii) to demonstrate how conservation genomics can be implemented in threatened species management. We conducted whole genome sequencing (WGS) of 25 individuals from the captive breeding programme and reduced-representation sequencing (RRS) of 98 founders of the same programme. A subset of the WGS samples was also sequenced by RRS, allowing u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 95 publications
(168 reference statements)
0
64
0
Order By: Relevance
“…This ~25% underestimation is probably due to the fact that ddRAD does not capture the most divergent genome sequences. However, the comparative value of heterozygosity rates estimated with ddRAD remains valid, as seen in other works (Wright et al 2020).…”
Section: Genomic Heterozygosity and Runs Of Homozygosity (Roh)mentioning
confidence: 61%
See 1 more Smart Citation
“…This ~25% underestimation is probably due to the fact that ddRAD does not capture the most divergent genome sequences. However, the comparative value of heterozygosity rates estimated with ddRAD remains valid, as seen in other works (Wright et al 2020).…”
Section: Genomic Heterozygosity and Runs Of Homozygosity (Roh)mentioning
confidence: 61%
“…Genomics can help to not only determine which specimens may be more or less appropriate for genetic rescue or captive breeding according to specific genomic health indicators of each individual (Supple and Shapiro 2018;Humble et al 2020;Wright et al 2020), but also to monitor future individuals sampled after the conservation actions to confirm if the measures employed are helping to improve the impoverished genomic health of the Pyrenean desman.…”
Section: Lessons From the Genome Of A Species With Extraordinary Inbrmentioning
confidence: 99%
“…Conservation genomics helped to identify the conservation implications of admixture in the Eastern wolf Canis lupus lycaon [ 165 ]. Wright et al [ 174 ] identified several candidate genes that may be associated with variation in the breeding success of the Tasmanian devil Sarcophilus harrisii . From the M. lutreola population genetics perspective, the same research demonstrated that individual heterozygosity was not associated with breeding success in captivity but was negatively associated with litter sizes of breeding females [ 174 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some workshop participants did not believe spatial mismatch is as much of an issue in 2019 as in 2014, likely because local‐level research is increasingly being translated into other contexts and at larger scales. For example, the Australasian Genomics Wildlife Group works to generate species‐specific conservation outcomes, such as for the Tasmanian devil, while also being recognized as a global leader for translating genomic tools to threatened species management around the world (Wright et al., 2020). Likewise, genomics studies of salmonid species demonstrate a range of successful research–practice collaborations that are context relevant while also providing translatable global insights (Garner et al., 2016; Piccolo, 2016).…”
Section: Spatial Mismatchmentioning
confidence: 99%